Transformation of the regulation of liability for tax offenses in the Russian Federation - E. L. Gulkova (Publishing House of the State University of Management, 2019)
The issues of changes in the tax legislation of the Russian Federation, the system of regulation of tax control in the application of liability for tax offenses have been raised. The problems of tax administration in the sphere of taxation have been considered, as well as the prospects and directions offurther development and expansion of the applied methods of management of tax relations in the Russian Federation have been determined. The ways of improving tax regulation and improving the efficiency of taxation and tax control in the transformation of the regulation of liability for tax offenses have been offered.